Quality of ‘Cripps Pink’ apples stored under controlled atmosphere with ultra-low and extremely low oxygen partial pressures or treated with 1-methylcyclopropene - Fernandes R.C.* (2021)
© 2021, Agronomic Institute of Campinas. All rights reserved.The objective of this work was to evaluate the effects of low, ultra-low, and extremely low partial pressures of O2 in a controlled atmosphere (CA) and 1-methylcyclopropene (1-MCP) on the postharvest quality of ‘Cripps Pink’ apples. The treatments used were 21.00 kPa of O2 (cold storage [CS]), CS + 1-MCP, and CA conditions with 2.00, 1.00, 0.60 and 0.25 kPa of O2, without 1-MCP. All fruit were stored at 1.5 ± 0.2 °C, relative humidity (RH) 92 ± 2%, and partial pressure of CO2 < 0.5 kPa, for 4.5 and 8 months, followed by another seven days of shelf life (20 ± 2 °C/RH of 60 ± 5%). Respiration and ethylene production rates were reduced in all CA conditions and the CS + 1-MCP treatment when compared to the CS without 1-MCP, in both storage periods. The application of 1-MCP delayed ripening and reduced the quality loss of the fruits stored for 4.5 months. The CA with 0.6 and 0.25 kPa of O2 reduced the incidence of superficial scald, decay, mealiness, and skin greasiness, and maintained the background color of the epidermis of the fruits in storage for 8 months. Among the CA conditions, the treatment of 0.25 kPa presented the highest production of ethanol and acetaldehyde in the fruits stored for 8 months. Treatment of 0.6 kPa of O2 kept higher values of total phenolic compounds, in the peel and flesh, in both storage periods. Fruits stored under 0.6 kPa of O2 showed the best quality after 8 months of storage.